Combination immunotherapy with interleukin‐2 surface‐modified tumor cell vaccine and programmed death receptor‐1 blockade against renal cell carcinoma. Issue 1 (1st December 2018) - Zhang, Xinji; Shi, Xiaojun; Li, Jinlong; Hu, Zhiming; Gao, Jimin; Wu, Shihao; Long, Zhaolin
Abstract : Immunotherapy may be an effective way to prevent postoperative recurrence of renal cell carcinoma. Streptavidin‐interleukin‐2 (SA‐IL‐2) surface‐modified tumor cell vaccine developed through our protein‐anchor technology could induce specific antitumor T‐cell responses, but this immunotherapy cannot completely eradicate the tumor. These effector T cells highly expressed programmed death receptor‐1 (PD‐1), and the expression of programmed death ligand‐1 (PD‐L1) in the tumor environment also was upregulated after SA‐IL‐2‐modified vaccine therapy. PD‐1/PD‐L1 interaction promotes tumor immune evasion. Adding PD‐1 blockade to SA‐IL‐2‐modified vaccine therapy increased the number of CD4 +, CD8 + and CD8 + interferon‐γ + but not CD4 + Foxp3 + T cells. PD‐1 blockade could rescue the activity of tumor‐specific T lymphocytes induced by the SA‐IL‐2‐modified vaccine. Combination therapy delayed tumor growth and protected mice against a second Renca cells but not melanoma cells challenge. Taken together, PD‐1 blockade could reverse immune evasion in the treatment with SA‐IL‐2‐modified vaccine, and eventually induce a stronger specific antitumor immune response against renal cell carcinoma. Abstract : Streptavidin‐interleukin‐2 surface‐modified tumor cell vaccine can induce tumor‐specific immune response, but this tumor cell vaccine treatment can not completely eradicate the tumor due to the immune evasion mediated by PD‐1/PD‐L1 signaling. PD‐1 blockade combined with the tumor cell vaccine could induce a stronger specific anti‐tumor immune response against renal cell carcinoma.